2016
DOI: 10.1051/0004-6361/201628944
|View full text |Cite
|
Sign up to set email alerts
|

Study of open clusters within 1.8 kpc and understanding the Galactic structure

Abstract: Context. Significant progress has been made in recent years to understand the formation and evolution of our Galaxy, but we still lack a complete understanding of the Galaxy and its structure. Aims. Using an almost complete sample of Galactic open star clusters within 1.8 kpc, we aim to understand the general properties of the open cluster system in the Galaxy and probe the Galactic structure. Methods. We first extracted 1241 open clusters within 1.8 kpc of the Sun from the Milky Way Star Clusters (MWSC) catal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 84 publications
10
70
0
Order By: Relevance
“…9 Recent estimates of  z range between +6 pc and +30 pc (Joshi et al 2016). Based on an analysis of nearby open clusters, Joshi et al (2016) obtained  = +  z 6.2 1.1 pc; we fix  z at +6.0 pc. The Galactic Cartesian coordinates of any object are (x, y,…”
Section: Components Of the Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…9 Recent estimates of  z range between +6 pc and +30 pc (Joshi et al 2016). Based on an analysis of nearby open clusters, Joshi et al (2016) obtained  = +  z 6.2 1.1 pc; we fix  z at +6.0 pc. The Galactic Cartesian coordinates of any object are (x, y,…”
Section: Components Of the Modelmentioning
confidence: 96%
“…Studies of the distribution of massive stars, molecular gas, and H II regions in the inner Galaxy (e.g., Nakanishi & Sofue 2006;Urquhart et al 2014;Anderson et al 2015) show that the gas density peaks at a Galactocentric radius of 4-5 kpc. Analyses of the z-distribution of tracers of high-density gas in the Galactic disk and spiral arms such as neutral hydrogen (H I; e.g., Kalberla et al 2007) and molecular gas (e.g., Nakanishi & Sofue 2006) give scale heights in the range 50-70 pc at Galactocentric radii of 4-6 kpc, whereas mid-infrared observations of massive stars in the Galactic disk (e.g., Urquhart et al 2014) and open star clusters (Joshi et al 2016) give scale heights less than half as large, 20-25 pc. 11 All of these tracers show an increasing scale height with increasing Galactocentric radius, with a pronounced flaring at radii 10 kpc.…”
Section: Thin Diskmentioning
confidence: 99%
“…Bonatto et al (2006) demonstrated that the scale height increases from 48±3 pc for open clusters younger than 200 Myr to 150±27 pc for clusters with ages up to 1 Gyr. Studying a larger sample of open clusters, Buckner & Froebrich (2014) and Joshi et al (2016) showed that this trend continues for older clusters; they found a scale height h 300 > pc for 2.5 Gyr and older clusters. Bovy et al (2012) used SEGUE G dwarfs to define monoabundance populations, and fit each population as a single exponential disk.…”
Section: The Disk Luminosity Functionmentioning
confidence: 97%
“…The distance and age of the Galactic OCs are important parameters in tracing the Galactic structure and chemical evolution of the Galaxy using OCs as tracers (Friel & Janes 1993;Joshi et al 2016). The CMD of the cluster play important role in identification of the member stars as well as determination of the cluster parameters like reddening, metallicity, age, and distance modulus.…”
Section: Age and Distance Through Cmdmentioning
confidence: 99%
“…The study of mass segregation in OCs can be carried out by studying mass distribution and variation in the slope of the MF with the radial distances (Lim et al 2013). The intermediate age OCs are spread in most regions of the Galactic disk and have a wide range in their ages (Joshi et al 2016), therefore, they are very important in the understanding of stellar evolution and dynamical evolution of the stars, particularly having intermediate to low masses.…”
Section: Introductionmentioning
confidence: 99%